Pengaruh Kecerdasan Emosional terhadap Perilaku Konsumtif pada Pengguna Aplikasi TikTok Shop - Vina Agustin; Ritno Andriyanto; Sinta Rizqiana; Khairani Zikrinawati; Zulfa Fahmy (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to determine the influence of emotional intelligence on consumptive behavior in users of the TikTok Shop application. One psychological factor, namely emotional, also influences financial decisions and financial markets. Someone who has not been able to maximize and control himself is less able to be wise in spending money. The method used in this study is a quantitative method using a non-experimental design. The data collection technique was by distributing questionnaires, namely the emotional intelligence scale consisting of 14 items and the consumer behavior scale consisting of 27 items. The scale is presented using a Likert scale in intervals of 1-5. In this research data analysis technique uses simple regression analysis with the help of SPSS software. The subjects in this study were users of the TikTok Shop application with an age range of 17-40 years. The data obtained from the results of distributing questionnaires to the subjects is that there is no significant influence between the influence of emotional intelligence on consumptive behavior in users of the TikTok Shop application with a sig value. 0.147<0.05. So the results of this study show that there is no influence between emotional intelligence on the consumptive behavior of users of the TikTok Shop application.